The Republic of Chile Public Expenditure Review - World Bank (World Bank, Washington, DC, 2020)
This Public Expenditure Review was prepared by the World Bank upon request from the Ministryof Finance of Chile. It identifies measures to improve the efficiency of public spending in a relatively narrow set of programs and functions in health, education and innovation and entrepreneurship. In health, the report recommends specific measures to improve the procurement of drugs and enhancing hospital efficiency. In education, efficiency gains can be achieved within government programs for school feeding, laptop distribution and text books. Interms of innovation and entrepreneurship programs, there is scope for further rationalization and consolidation of programs and processes, especially at the design stage. If implemented, these measures could result in cost savings of CLP284 billion (US$422 million), equivalent to 0.2 percent of GDP or about three quarters of the fiscal adjustment targeted for 2016.